Analysis of the Role of PAI Subject Teachers in Controlling Difficulties in Reading Al-Qur'an at SMK Negeri 1 Tebing Tinggi - Sindy Rahmawati (AR-RASYID : Jurnal Pendidikan Agama Islam, 2023)
Teaching to read the Qur'an is an obligation for every parent to his child. Children should be taught to read the Qur'an at an early age. But lately, in the midst of society that lives in a modern style, they often forget the importance of teaching the Qur'an to children. Moreover, in terms of quantity, the Muslim community, especially among teenagers, is experiencing quite adequate conditions. It is very ironic with the condition of the people in Indonesia, the majority of whom are Muslims. In a situation like this, one of the ways that parents take is to send their children to educational institutions to ease their duties as parents. So they fully trust the school to guide their children. sometimes they don't want to know their child's progress in reading the Qur'an because they trust the school. One component that is directly responsible for fostering students' ability to read the Qur'an is the Islamic religion teacher. This is where Islamic religious teachers play their best role in order to achieve this. However, he must continue to cooperate with other parties such as school principals and homeroom teachers. A religious teacher must be creative and innovative in anticipating the development of the times which are increasingly making children away from the Qur'an. The purpose of this study was to determine the form of students' difficulties in reading the Qur'an at SMK Negeri 1 Tebing Tinggi, as well as to determine the factors causing students' difficulties in reading the Qur'an and how the PAI teachers' efforts in overcoming students' difficulties in reading Al-Qur'an. Qur'an. Qur'an at SMK Negeri 1 Tebing Tinggi.